A framework for multi-UAV software in the loop simulations. (2018) - Santana, Ernesto; Moreno, Romualdo; Sánchez, Christian; Piera, Miquel Àngel
In this paper, we present a software-in-the-loop simulation framework for multi-UAV systems which allows test the implementation of single or multi-UAV applications, including different cooperation algorithms, sense and avoid algorithms, etc. without taking any risk. In our proposed framework, we can test the correct execution of algorithms and since our setup is inherently multi-UAV, we can also test the communication flow among the vehicles. The simulation framework has been developed as a functional extension of mission planner, open source software aimed to plan, control and analyse data from missions of a single UAV driven by Ardupilot flight controllers.